A review on methods for liberating lithium from pegmatities. (1st January 2020) - Karrech, A.; Azadi, M.R.; Elchalakani, M.; Shahin, M.A.; Seibi, A.C.
Highlights: Main global resources and reserves of lithium. Processes of lithium extraction from hard rocks. Comparison between existing and emerging lithium extraction processes. Abstract: The increasing demand for smart devices and clean energy vehicles that use lithium-ion batteries has sparked a considerable interest in lithium, which is becoming a strategic element. Lithium deposits can be found in saline lacustrine environments or pegmatite hard-rocks that are located mainly in America (Argentina, Bolivia, Chile, USA, and Canada), Australia (Western Australia), and China. In this paper, we summarise the main approaches of lithium extraction from pegmatites. Well established processes such as calcination, roasting, chlorination, carbonate pressure leaching, caustic/acidic digestion and others are examined and discussed to reflect their significance to the modern lithium value chain. In addition, emerging processes that involve direct mechano-chemical activation, bioleaching, acidic or caustic leaching are evaluated and compared to proven approaches in terms of economical and environmental viability. This review indicates that while established processes are still appealing to the industry despite their excessive energy requirement, new processes may contribute significantly to modernising lithium extraction in the future.